2016
DOI: 10.3892/etm.2016.2984
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone IIA enhances chemosensitivity of colon cancer cells by suppressing nuclear factor-κB

Abstract: Abstract. The aim of the present study was to investigate the effect and molecular mechanism of tanshinone IIA (TSA) on colon cancer cells. Cell viability was determined using Cell Counting kit-8 assay and the results demonstrated that TSA treatment significantly decreased the cell viability of HCT1116 and COLO205 cells in a dose-dependent manner. TSA treatment also sensitized HCT1116 and COLO205 cells to fluorouracil therapy in a concentration-dependent manner. Western blotting was performed in order to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…Tanshinone IIA is shown to enhance chemosensitivity and its efficacy when combined with other therapeutic agents. Tanshinone IIA can be an effective adjunctive agent in cancer, and it enhances the chemosensitivity to 5-fluorouracil therapy in human colorectal cancer HCT-1116 and COLO-205 cells through NF-κB inhibition [539]. The combination of tanshinone IIA with doxorubicin does not only enhance the chemosensitivity of doxorubicin, but also reduces the toxic side effects of doxorubicin in human breast cancer MCF-7 cells [540].…”
Section: Tanshinonesmentioning
confidence: 99%
“…Tanshinone IIA is shown to enhance chemosensitivity and its efficacy when combined with other therapeutic agents. Tanshinone IIA can be an effective adjunctive agent in cancer, and it enhances the chemosensitivity to 5-fluorouracil therapy in human colorectal cancer HCT-1116 and COLO-205 cells through NF-κB inhibition [539]. The combination of tanshinone IIA with doxorubicin does not only enhance the chemosensitivity of doxorubicin, but also reduces the toxic side effects of doxorubicin in human breast cancer MCF-7 cells [540].…”
Section: Tanshinonesmentioning
confidence: 99%
“…The mechanism studies demonstrated that suppression of kinase activity and downregulation of the protein level of oncogenetic transcription factors were involved in the Tan IIA-mediated antitumor effect. [15][16][17][18][19] However, the function of Tan IIA on EGFR signaling and the mechanisms of how Tan IIA inhibits human NSCLC cancer cells remain undefined.…”
Section: Introductionmentioning
confidence: 99%
“…Bai et al . (2016) found that through the suppression of the NF‐κB signaling pathway, TSN IIA could lead to the death of colon cancer cells [40]. In summary, it indicates that TSN IIA attenuates DNP by promoting the expression of Nrf2/ARE signaling pathway‐related genes and inhibiting the expression of NF‐κB signaling pathway‐related genes.…”
Section: Discussionmentioning
confidence: 98%